Implementación préstamo personal CAFAE sector educación - Moreno Wong, José Carlos (2021)
The present investigation is an implementation of the Personal Loan at Banco ABC (fictitious name that was chosen to protect the confidentiality of the real bank where I worked) through a public agreement with the Management Committee of the Stimulus Assistance Fund for the Education Sector (CAFAE SE). The initiative for the implementation of the CAFAE SE agreement was born because, at the beginning of the first half of 2018, CAFAE SE decided not to renew the commercial agreement it had with another local bank, putting it to an end in June of that same year, leaving the Bank ABC with the possibility of negotiating and carrying out the agreement, generating the need to implement this new business model tailored to the processes and service times established by CAFAE SE. This agreement would help the bank to achieve one of the strategic objectives of 2018, which was the 10% increase (S / 380 million) in loans placed.